INTERNATIONAL ISLAMIC CURRICULUM MANAGEMENT IN FOSTERING HOLISTIC, HARMONIOUS, AND EXEMPLARY EDUCATION AT AL WAFI ISLAMIC BOARDING SCHOOL - Kuncoro, Irfan (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
This research discusses the management of international Islamic-based curriculum at Al Wafi Islamic Boarding School which plays an important role in creating holistic, harmonious, and exemplary education. The purpose of this research is to explore the concept, internalisation process, and implications of the curriculum management. Through this approach, Al Wafi has succeeded in integrating global education standards with Islamic values, forming students who are scientifically proficient, have self-awareness, and high social responsibility. This research uses a qualitative method with data collection through focus group discussions (FGDs), interviews, observation, and documentation. This method allows researchers to understand the implementation of a curriculum that combines the intellectual, spiritual, physical, and emotional aspects of students. The results showed that: 1) The concept of international Islamic standard curriculum management at Al Wafi serves to build a holistic and harmonious education, creating students who are scientifically proficient, have self-awareness, and high social responsibility; 2) The internalisation of the curriculum is designed to create a comprehensive education that includes intellectual, spiritual, physical, and emotional aspects, by integrating general science and Islamic values; 3) The implications of this curriculum management show a significant impact in shaping the character of students who are tolerant, caring, and have Islamic principles, so that graduates are expected to be able to face global challenges while upholding Islamic values